ANALYSIS OF MENTAL NURSING CARE IN SCHIZOPHRENIC PATIENTS WITH THE APPLICATION OF OCCUPATIONAL THERAPY (SPARE TIME) TO OVERCOME LOW SELF-ESTEEM - Anugrah Lestari; Khamida; Budury, Syiddatul; Wardani, Erika Martining (Nurse and Holistic Care, 2024)
Introduction: People with low self-esteem usually judge themselves negatively, feel guilty, feel useless, and feel insignificant. If this is not handled properly and quickly it will cause problems such as committing suicide, injuring others, and damaging the environment. Objective: The purpose of this study is to describe the analysis of nursing care in schizophrenic patients with the application of occupational therapy (free time) to overcome the problem of low self-esteem at Menur Hospital in Surabaya. Methods: The case study design with the subject Mrs. D with low self-esteem problems, was carried out 2 times in occupational therapy (free time) for 30 minutes in 2 days. Data collection techniques were used through direct observation and interviews using mental nursing care sheets. Before and after the application of occupational therapy, an assessment was carried out through direct observation and interviews. Results: The results of the evaluation after occupational therapy showed that there was a decrease in signs and symptoms of low self-esteem and an increase in the ability to increase self-esteem, such as increasing positive self-assessment, feeling worthless, and feelings of being unable to do anything decreased. Conclusions: This case study shows that leisure occupational therapy (flower arranging) can reduce signs and symptoms of low self-esteem. The conclusion from this study is that the application of leisure time occupational therapy can be used to overcome low self-esteem in schizophrenic patients. The role of the nurse is to provide nursing care and education to the patient's family about occupational therapy in their spare time.